1999
DOI: 10.1073/pnas.96.22.12822
|View full text |Cite
|
Sign up to set email alerts
|

The inv(16) encodes an acute myeloid leukemia 1 transcriptional corepressor

Abstract: The inv(16) is one of the most frequent chromosomal translocations associated with acute myeloid leukemia (AML). The inv(16) fusion protein acts by dominantly interfering with AML-1͞core binding factor ␤-dependent transcriptional regulation. Here we demonstrate that the inv(16) fusion protein cooperates with AML-1B to repress transcription. This cooperativity requires the ability of the translocation fusion protein to bind to AML-1B. Mutational analysis and cell fractionation experiments indicated that the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 37 publications
1
89
2
1
Order By: Relevance
“…RUNX1 residues 1-204 are also retained in the t(8;21) fusion protein, which again predicts that this fusion protein can recruit SUV39H1, although this association may negatively affect DNA binding (Chakraborty et al, 2003). Although the inv(16) contains no homology to RUNX1, it acts as a corepressor for RUNX1 (Lutterbach et al, 1999;Durst et al, 2003). Our initial analysis failed to detect an association between SUV39H1 and the inv(16) fusion protein.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…RUNX1 residues 1-204 are also retained in the t(8;21) fusion protein, which again predicts that this fusion protein can recruit SUV39H1, although this association may negatively affect DNA binding (Chakraborty et al, 2003). Although the inv(16) contains no homology to RUNX1, it acts as a corepressor for RUNX1 (Lutterbach et al, 1999;Durst et al, 2003). Our initial analysis failed to detect an association between SUV39H1 and the inv(16) fusion protein.…”
Section: Discussionmentioning
confidence: 83%
“…To begin to dissect the function of the subdomains that contact HDACs and SUV39H1, we performed reporter assays using the p21 cyclin-dependent kinase inhibitor promoter linked to firefly luciferase, which contains multiple RUNX1-binding sites (Lutterbach et al, 1999;Durst et al, 2003). RUNX1 was able to repress this promoter up to five-fold in the absence of its co-factor CBFb, and the co-expression of CBFb stimulated RUNX1-mediated repression to nearly 10-fold (Figure 6d).…”
Section: Histone Deacetylases Also Contact Rd2mentioning
confidence: 99%
See 1 more Smart Citation
“…35,47,48 Sitedirected mutation study elucidates Ser 249 , Thr 273 , and Ser 276 as the targets of phosphorylation. Computer software analysis of the signature motifs returned several candidate kinases that could be responsible for this phosphorylation, including MAPK, GSK3, and members of the CDK family.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning of the breakpoint for this translocation identified the fusion protein CBFb-SMMHC (Liu et al, 1993). Similar to AML1-ETO, CBFb-SMMHC functions as a dominant-negative inhibitor of AML1 transcriptional activity (Lutterbach et al, 1999). To date, there have been more than 12 different translocations identified that target the CBF complex, accounting for 25% of all AML (Speck and Gilliland, 2002).…”
Section: Differentiationmentioning
confidence: 99%